Platforms, data and children's rights: Introducing a 'networked capability approach'. (May 2017) - Swist, Teresa; Collin, Philippa
In this article, we consider the role of digital platforms for producing data and shaping how children's rights are understood, monitored and advocated for. We present a typology of platforms impacting children's rights, followed by the introduction of a 'networked capability approach'. A case study is used to explore the potential of this approach for examining the purpose, practices and repercussions of digital platforms. We argue that to recognize and actualize children's rights in a digital age, we need new conceptual tools to examine the interplay of platforms, people and places that include and exclude children's valued 'doings and beings'.